2020
DOI: 10.1093/icvts/ivaa296
|View full text |Cite
|
Sign up to set email alerts
|

Immune profiling after minimally invasive lobectomy

Abstract: OBJECTIVES Whether acute phase and immune responses are minimally affected following minimally invasive lung surgery needs further investigation. We performed a pilot study to evaluate the immune profile of patients who underwent video-assisted thoracoscopic surgery or robot-assisted thoracic surgery lobectomies for the treatment of suspicious or known stage I non-small-cell lung cancer. METHODS Blood samples were taken preop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Our results suggest VATS induces a more pronounced inflammatory response than robot-assisted, as demonstrated by measurements of pro-inflammatory cytokines IL-6 and MCP-1 (27,28). These particular findings suggest a greater degree of surgical trauma-induced systemic inflammation as the VATS elevated cytokines have all been strongly associated with thoracic surgery trauma (11)(12)(13). Indeed, elevated of pro-inflammatory cytokines, such as IL-6, have been extensively correlated with the degree of cutaneous trauma and subsequently elicited systemic inflammation throughout the repair process (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Our results suggest VATS induces a more pronounced inflammatory response than robot-assisted, as demonstrated by measurements of pro-inflammatory cytokines IL-6 and MCP-1 (27,28). These particular findings suggest a greater degree of surgical trauma-induced systemic inflammation as the VATS elevated cytokines have all been strongly associated with thoracic surgery trauma (11)(12)(13). Indeed, elevated of pro-inflammatory cytokines, such as IL-6, have been extensively correlated with the degree of cutaneous trauma and subsequently elicited systemic inflammation throughout the repair process (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 56%
“…In terms of design and control, our study seemed to have benefited from surgeon consistency as, unlike the majority of previous studies, we had no difference in operation time between VATS and robotic (3,(21)(22)(23)(24)(25). Additionally, while select previous studies presented statistically significant inter-cohort age differences, we found no difference between our robotic and VATS cohorts (13,26). Thus, we were able to more adequately isolate surgical approach as our exposure variable.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The perioperative results of RATS are similar to those of the VATS, as noted in a meta-analysis ( 40 ), but the length of the surgery in some cases can be longer after RATS than after VATS. There were no differences in acute phase proteins and immune responses between the RATS and VATS procedures ( 41 ), showing that surgical trauma is similar in the two MITS methods.…”
Section: Impact Of the Surgical Approach On Simentioning
confidence: 94%